FAKTOR-FAKTOR YANG MEMENGARUHI TERJADINYA DUPLIKASI PENOMORAN REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH DATU BERU TAHUN 2020 - Sri Agustina Meliala; Dyna Safitri Rakhelmi Rangkut; Rizki Sumanjaya (POLITEKNIK PIKSI GANESHA, 2022)
Background; Based on an initial survey conducted by researchers on December 27, 2019 at the Medical Record unit at the Regional General Hospital Datu Beru by conducting interviewa and observations on medical record officers. As for the results of the interviewand observations made that there is a number patients in 2019 as much 25.428 outpatient. From the results of interviews conducted, medical record officer said that in one month can be found 50 medical record file happens is duplication of medical record numbers. Objectives; to know influencing factors medical record numbering duplication at the local general hospital Datu Beru. Method; this research is analytical survey by design cross sectional. The population of this study is all medical record officers as much as 38 respondent which is also used as a research sample, test used chi-square. Results; test chi-square shows all education variables p = 0,796 have no influence, knowledge p = 0,000, experience p = 0,000 and system p = 0,001 have an influence on medical record numbering duplication. Conclusion; there is an influence of knowledge, experience and system against duplication of medical record numbering at the local general hospital datu beru. Keywords: education, knowledge, experience, medical record numbering duplication system